Mycofloral Pattern and Its Insights of Bioactive Compounds Against Pathogens: Life Sciences-Botany - Rajathi, S.; Murugesan, S.; Babu, S.; Shijila Rani , A.S.; Ambikapathy, V.; Prakash, P.; Panneerselvam, A. (International Journal of Life Science and Pharma Research, 2023)
Soil is considered a well-studied ecological niche for microorganisms that produce beneficial physiologically active natural compounds suited for medicinal purposes. The current study sought to elucidate antifungal activity and metabolism from fungi. The paddy field mycofloral diversity pattern was analyzed from the soil, and its physiochemical characteristics were also determined from the Kanyakumari district, Tamil Nadu, from 2016-2017. Totally twenty-seven fungal species were isolated from the paddy field soil. The physicochemical parameters of temperature, moisture content, pH, organic carbon, organic matter, and organic nitrogen were analyzed with significantly correlated. The most dominant fungal species include Aspergillus flavipes, A.flavus, A.fumigatus, A.nidulans, A.niger, A.ochraceous, Curvularia lunata, Fusarium solani, Saccharomyces cerevisiae, and Trichoderma viride were identified. Natural Products (NPs) synergistic effect was exploited to discover pairwise combinations with potential antifungal activity. A high-throughput screening approach with yeast revealed that NPs in molecules are the most promising novel synergies, namely, EUG+BER. This combination synergistically inhibits fungi, including human and crop pathogens such as Candida albicans, Aspergillus fumigatus, Zymoseptoria tritici, and Botrytis cinerea. This study was about screening pairwise NPs interactions as a tool to find novel antifungal synergies with the potential. Also, improved specificity may help manage fungal pathogens.